Rapid X-ray variability in Mkn 421 during a multiwavelength campaign. Issue 2 (7th April 2022) - Markowitz, Alex G; Nalewajko, Krzysztof; Bhatta, Gopal; Dewangan, Gulab C; Chandra, Sunil; Dorner, Daniela; Schleicher, Bernd; Pajdosz-Śmierciak, Urszula; Stawarz, Łukasz; Zola, Staszek; Ostrowski, Michał; Carosati, Daniele; et al.
ABSTRACT: The study of short-term variability properties in AGN jets has the potential to shed light on their particle acceleration and emission mechanisms. We report results from a 4-d coordinated multiwavelength campaign on the highly peaked blazar (HBL) Mkn 421 in 2019 January. We obtained X-ray data from AstroSAT, BVRI photometry with the Whole Earth Blazar Telescope (WEBT), and TeV data from First G-APD Cherenkov Telescope to explore short-term multiwavelength variability in this HBL. The X-ray continuum is rapidly variable on time-scales of tens of ks. Fractional variability amplitude increases with energy across the synchrotron hump, consistent with previous studies; we interpret this observation in the context of a model with multiple cells whose emission spectra contain cutoffs that follow a power-law distribution. We also performed time-averaged and time-resolved (time-scales of 6 ks) spectral fits; a broken power-law model fits all spectra well; time-resolved spectral fitting reveals the usual hardening when brightening behaviour. Intra-X-ray cross-correlations yield evidence for the 0.6–0.8 keV band to likely lead the other bands by an average of 4.6 ± 2.6 ks, but only during the first half of the observation. The source displayed minimal night-to-night variability at all wavebands thus precluding significant interband correlations during our campaign. The broad-band SED is modelled well with a standard one-zone leptonic model, yielding jet parameters consistent with those obtained from previous SEDs of this source.